Edwardsiella tarda septicaemia in a calf - Magalhães, Helena; Freitas, Maria do Amparo Queiroz de; Santos, Jefferson Andrade dos; Costa, Carlos Henrique Campello (Pesquisa Agropecuaria Brasileira, 2014)
During research on diseases of calves at Cantagalo, RJ, Brazil, Edwardsiella tarda was isolated from the bone marrow, lung, spleen, liver and bile of a 10 -day old calf with diarrhea,anorexia, feebleness and cachexia. The histopathologic examination revealed omphalophlebitis at the level of the umbilical cord. This is the first report of isolation of Edwardsiella tarda from bovines in Brazil.